Genetics of Acquired Antibiotic Resistance Genes in Proteus spp. - Girlich, Delphine; Bonnin, Rémy A.; Dortet, Laurent; Naas, Thierry (Frontiers in Microbiology, 2020)
Proteus spp. are commensal Enterobacterales of the human digestive tract. At the same time, P. mirabilis is commonly involved in urinary tract infections (UTI). P. mirabilis is naturally resistant to several antibiotics including colistin and shows reduced susceptibility to imipenem. However higher levels of resistance to imipenem commonly occur in P. mirabilis isolates consecutively to the loss of porins, reduced expression of penicillin binding proteins (PBPs) PBP1a, PBP2, or acquisition of several antibiotic resistance genes, including carbapenemase genes. In addition, resistance to non-β-lactams is also frequently reported including molecules used for treating UTI infections (e.g., fluoroquinolones, nitrofurans). Emergence and spread of multidrug resistant P. mirabilis isolates, including those producing ESBLs, AmpC cephalosporinases and carbapenemases, are being more and more frequently reported. This review covers Proteus spp. with a focus on the different genetic mechanisms involved in the acquisition of resistance genes to multiple antibiotic classes turning P. mirabilis into a dreadful pandrug resistant bacteria and resulting in difficult to treat infections.